Analisis Hubungan Kekerabatan Antara Bahasa Sabu, Sumba, dan Rote dalam Konteks Linguistik - Reyneldis B. Fernandez; Sebastianus Fernandez (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine the kinship between the Sabu, Sumba, and Rote languages, which are regional languages spoken in East Nusa Tenggara, Indonesia. Geographically, these three languages are spoken in different areas, originating from three distinct islands, with each having its own unique linguistic characteristics. Based on linguistic classification, the Rote and Sabu languages belong to the Ambon–Timor subgroup, while the Sumba language is classified under the Bima–Sumbawa subgroup. Despite these differences, there are noticeable signs of linguistic kinship, including cultural elements such as similarities in the clan naming system, which suggests a potential historical connection among these languages. To investigate this further, the research gathered data from native speakers of the three languages, who provided verbal samples that were transcribed phonetically. Lexicostatistics was then applied to analyze the vocabulary and determine the percentage of kinship between the languages. This method involves comparing common words in each language and quantifying the level of similarity. The findings of this study are expected to contribute to a clearer understanding of the linguistic relationships between Sabu, Sumba, and Rote. The results will offer insights into whether these languages share a common ancestral root or if their similarities are due to cultural exchange and contact over time. This research also aims to highlight the importance of preserving these regional languages, as understanding their kinship could play a role in the revitalization of linguistic heritage in East Nusa Tenggara. The study's results are anticipated to enrich the field of comparative linguistics, particularly in relation to the Austronesian language family, and provide valuable information for future studies on language development in Indonesia.